National risk prediction model for perioperative mortality in non‐cardiac surgery. Issue 11 (6th August 2019) - Campbell, D.; Boyle, L.; Soakell‐Ho, M.; Hider, P.; Wilson, L.; Koea, J.; Merry, A. F.; Frampton, C.; Short, T. G.
Abstract : Background: Many multivariable models to calculate mortality risk after surgery are limited by insufficient sample size at development or by application to cohorts distinct from derivation populations. The aims of this study were to validate the Surgical Outcome Risk Tool (SORT) for a New Zealand population and to develop an extended NZRISK model to calculate 1‐month, 1‐year and 2‐year mortality after non‐cardiac surgery. Methods: Data from the New Zealand National Minimum Data Set for patients having surgery between January 2013 and December 2014 were used to validate SORT. A random 75 per cent split of the data was used to develop the NZRISK model, which was validated in the other 25 per cent of the data set. Results: External validation of SORT in the 360 140 patients who underwent surgery in the study period showed good discrimination (area under the receiver operating characteristic curve (AUROC) value of 0·906) but poor calibration (McFadden's pseudo‐ R 2 0·137, calibration slope 5·32), indicating it was invalid in this national surgical population. Internal validation of the NZRISK model, which incorporates sex and ethnicity in addition to the variables used in SORT for 1‐month, 1‐year and 2‐year outcomes, demonstrated excellent discrimination with AUROC values of 0·921, 0·904 and 0·895 respectively, and excellent calibration (McFadden's pseudo‐ R 2 0·275, 0·308 and 0·312 respectively). Calibration slopes were 1·12, 1·02 and 1·02 respectively. Conclusion: The SORT performed poorly in this national population. However, inclusion of sex and ethnicity in the NZRISK model improved performance. Calculation of mortality risk beyond 30 days after surgery adds to the utility of this tool for shared decision‐making. Abstract : A new national non‐cardiac risk calculator for 1‐month, 1‐year and 2‐year mortality was validated for a New Zealand surgical population. It is one of the most accurate risk tools developed to date. Ethnicity changes risk Abstract : Antecedentes: Muchos modelos multivariados de estimación del riesgo de mortalidad después de la cirugía están limitados por haberse desarrollado a partir de tamaños muestrales insuficientes o por haberse aplicados a cohortes distintas de las poblaciones de derivación. Los objetivos de este estudio fueron validar el Surgical Outcome Risk Tool (SORT) para una población de Nueva Zelanda y desarrollar un modelo NZRISK extendido para calcular la mortalidad al mes y a los 1 y 2 años de una cirugía no cardíaca. Métodos: Para validar el SORT se utilizó el Conjunto Mínimo Básico de Datos de Nueva Zelanda para los pacientes sometidos a cirugía entre enero de 2013 y diciembre de 2014. Se realizó una división aleatoria del 75% de los datos para desarrollar el modelo NZRISK que, posteriormente, se validó en el otro 25% del conjunto de datos. Resultados: La validación externa de SORT en 360.140 pacientes intervenidos en el periodo analizado mostró una buena discriminación (área bajo las curvas de característica operativa del receptor ( area under the receiver‐operator characteristic curves (AUROC) 0, 906)) pero con una mala calibración (pseudo‐R 2 de McFaddens 0, 137 y pendiente de calibración 5, 32), lo que indicaba que SORT no era válido para esta población quirúrgica nacional. La validación interna del modelo NZRISK, que incorpora el género y la etnia además de las variables utilizadas en el SORT, para los resultados al mes y a los 1 y 2 años demostró una excelente capacidad de discriminación con una AUROC de 0, 921, 0, 904, 0, 895 respectivamente y una calibración excelente, con una pseudo‐R 2 de McFaddens de 0, 275, 0, 308 y 0, 312 respectivamente. Las pendientes de calibración fueron de 1, 12, 1, 02 y 1, 02, respectivamente. Conclusión: El SORT no fue útil en esta población nacional. Sin embargo, la inclusión del género y la etnia en el modelo NZRISK mejoró sus resultados. El cálculo del riesgo de mortalidad más allá de 30 días después de la cirugía añade utilidad a esta herramienta para la toma de decisiones compartida.